PPARG is central to the initiation and propagation of human angiomyolipoma, suggesting its potential as a therapeutic target. Issue 4 (8th March 2017) - Pleniceanu, Oren; Shukrun, Racheli; Omer, Dorit; Vax, Einav; Kanter, Itamar; Dziedzic, Klaudyna; Pode‐Shakked, Naomi; Mark‐Daniei, Michal; Pri‐Chen, Sara; Gnatek, Yehudit; Alfandary, Hadas; Varda‐Bloom, Nira; et al.
Abstract: Angiomyolipoma (AML), the most common benign renal tumor, can result in severe morbidity from hemorrhage and renal failure. While mTORC1 activation is involved in its growth, mTORC1 inhibitors fail to eradicate AML, highlighting the need for new therapies. Moreover, the identity of the AML cell of origin is obscure. AML research, however, is hampered by the lack of in vivo models. Here, we establish a human AML‐xenograft (Xn) model in mice, recapitulating AML at the histological and molecular levels. Microarray analysis demonstrated tumor growth in vivo to involve robust PPARG‐pathway activation. Similarly, immunostaining revealed strong PPARG expression in human AML specimens. Accordingly, we demonstrate that while PPARG agonism accelerates AML growth, PPARG antagonism is inhibitory, strongly suppressing AML proliferation and tumor‐initiating capacity, via a TGFB‐mediated inhibition of PDGFB and CTGF. Finally, we show striking similarity between AML cell lines and mesenchymal stem cells (MSCs) in terms of antigen and gene expression and differentiation potential. Altogether, we establish the first in vivo human AML model, which provides evidence that AML may originate in a PPARG‐activated renal MSC lineage that is skewed toward adipocytes and smooth muscle and away from osteoblasts, and uncover PPARG as a regulator of AML growth, which could serve as an attractive therapeutic target. Synopsis: Angiomyolipoma (AML) research is hampered by the lack of an animal model. In a novel in vivo human AML model, PPARG inhibition is identified as a potential therapy and the AML cell of origin as a resident MSC/pericyte skewed toward adipogenic differentiation. An AML xenograft (Xn) model, exhibiting the classic histology, immunophenotype, and gene expression pattern of human AML, was established by injection of human AML cells in mice. AML Xn propagation in vivo is accompanied by robust activation of the PPARG pathway, and human AML tumors strongly express PPARG. PPARG is expressed across all tumor compartments, indicating that rather than accompanying adipocytic differentiation, PPARG activation drives AML growth, and with the presence of fat in the tumor being its by‐product. PPARG antagonism, via small molecules and shRNA, results in strong growth inhibition of AML, as well as abrogation of tumor initiation in mice. Human AML cells exhibit striking similarity to human MSCs, in terms of gene expression, surface marker expression, and potential. Abstract : Angiomyolipoma (AML) research is hampered by the lack of an animal model. In a novel in vivo human AML model, PPARG inhibition is identified as a potential therapy and the AML cell of origin as a resident MSC/pericyte skewed toward adipogenic differentiation.